Synthesis of Enantiopure 2‐Alkyl‐1, 3, 3‐Trinitroazetidines. (29th July 2019) - Ha, Heun‐Jong; Lee, Su‐Jeong; Chang, Duk‐Ho; Lee, Hyo‐Jun; Kim, Bora; Kim, Seung Hee; Kim, Jin Seuk; Cho, Chang‐Woo
Abstract : Enantiopure 2‐alkyl‐1, 3, 3‐trinitroazetidines4 were efficiently synthesized by the nitrolysis of enantiopure 2‐alkyl‐3, 3‐dinitro‐1‐tosylazetidines3 using an excess of fuming nitric acid in CHCl3 at ambient temperature. In addition, elaboration of ( S )‐2‐(2‐methoxyethyl)‐1, 3, 3‐trinitroazetidine (4c ) was successfully performed to synthesize a variety of enantiopure 2‐alkyl‐1, 3, 3‐trinitroazetidines5 –7 . The advantage of this strategy is that 2‐alkyl‐1, 3, 3‐trinitroazetidines can be synthesized either asymmetrically or racemically depending on the presence or absence of chirality in N ‐sulfinyl aldimines2 used as the starting material. Furthermore, the sensitivity measurement results of racemic 2‐methyl‐1, 3, 3‐trinitroazetidine (racemic4a ) showed that the introduction of an alkyl substituent at the C2 position of 1, 3, 3‐trinitroazetidine had a significant effect on the sensitivity of the resulting 2‐alkyl‐1, 3, 3‐trinitroazetidine. Abstract : Efficient synthesis of various enantiopure 2‐alkyl‐1, 3, 3‐trinitroazetidines.